Causes of arrested succession in coastal dune forest - (:unkn) unknown (My University, 2011)
Dispersal or recruitment limitation may arrest succession after disturbance. In north-eastern South Africa the Acacia karroo successional pathway is used to facilitate coastal forest recovery after strip-mining. However, although A. karroo establishes naturally, it forms monospecific stands, arresting forest succession for decades. This casts doubt on the efficacy of this restoration pathway. We investigated the causes of arrested succession. The seed and seedling banks of A. karroo stands and of forest at Cape Vidal, and three A. karroo stands (7-27 years old) on rehabilitated strip-mined dunes at nearby Richards Bay were examined. The establishment and growth of seedlings at Cape Vidal were also considered. The seed bank was larger and more diverse in forest, but the seedling bank was larger in Acacia stands. At Richards Bay, the size of the seed bank increased and the seedling bank decreased with Acacia stand age. Excluding mammalian herbivores in Acacia stands at Cape Vidal resulted in greater species richness and survival of naturally established seedlings, as well as two experimentally planted species. Neither seed dispersal nor seedling establishment limited recruitment of tree species in Acacia stands. Herbivory arrested forest succession by causing the differential mortality of seedlings. In contrast, at Richards Bay where there were few mammalian herbivores, the advanced regeneration in A. karroo stands converged on the diversity of nearby forests 29 years after restoration. Controlling herbivore access and seeding Acacia stands with forest species are site-specific options for preventing arrested succession when using the A. karroo successional pathway.
Keywords: African Research